Perceived leadership integrity and organisational commitment - Nangoli, Sudi; Muhumuza, Benon; Tweyongyere, Maureen; Nkurunziza, Gideon; Namono, Rehema; Ngoma, Muhammed; Nalweyiso, Grace (Journal of Management Development, 2020)
The purpose of this paper is to investigate the extent to which perceived leadership integrity influences changes in organisational commitment. The premise of the study is the argument that non-financial rewards alleviate the challenges associated with low levels of commitment in economies that are riddled with incessant situations of economic scarcity. Design/methodology/approach – An explanatory study approach was adopted to investigate the envisaged linkage between the study variables from a socio-psychological perspective. Findings – The results of the study establish that perceived leadership integrity significantly influences variations in commitment among organisational employees. Research limitations/implications – The study results provide a reason for firms to invest more resources towards promoting honesty among organisational leaders. The findings of the study support the idea that perceived integrity of an organisation’s leadership generates a sustainable win–win position not only between the organisation and employees, but also among the leaders and subordinates. Practical implications – Organisations must regularly consider the drivers of organisational commitment and pay sufficient attention to non-financial drivers. As advanced by this study, a very important yet economical way of effecting such a strategy is through instituting measures that sustainably create a perception among employees that organisational leaders execute their duties with the utmost integrity. Originality/value – This article has both empirical and theoretical value. Empirically, this work is the first of its kind aimed at investigating the effect of perceived leadership integrity on organisational commitment within Uganda’s hospitality setting. Theoretically, the study extends the versatility of the hierarchy of needs theory by clarifying that higher-level needs offer a basis for explaining the effect of psychological processes (in this case, perceived leadership integrity) on behavioural changes (in this case, organisational commitment).
Keywords: Perceived leadership integrity; Organisational commitment; B-needs; Human resource